Assessment of the defendants’ mental state in the Units against Flagrante delicto - Bustamante Maita, Sherly Tania (2022)
Due diligence demands that justice servers reduce risks in their acts of investigation and prosecution, being one of their purposes not to violate the fundamental rights. The Units against Flagrante Delicto are also governed by this principle; therefore, it is important to demonstrate technically and scientifically that those accused of a flagrante crime be in a sound state of mind. This procedure must be carried out by forensic psychologists in said units, as its implementation requires the use of specialized knowledge. Because of the nature of the examination, it can be carried out in a short time, and when there are clear results from this procedure, it will be possible to ensure that the accused is aware of their actions. Besides, these results will prevent the accused from simulating a mental disorder in the future to get a reduced sentence.